Fatores que envolvem o alcance da maternidade por meio de material genético de terceiros - Lozzo, Claudia Ines Aparecida da [UNIFESP] (2017)
Introduction: Women who can’t get pregnant or face some difficulties for it, sometimes search for assisted reproduction techniques (AHR). To make the decision to use the Assisted Human Reproduction (AHR) with the donation of oocyte, requires the breaking of paradigms and representations of blood / genetic transmission and the acceptance of the idea that having a child means the experience of pregnancy and birth. Considering AHR a different and controversial contemporary theme, interested women can search for private clinics, hospitals and public information in social medias, blogs and websites that will help them making their decision. Objective: The purpose of this research is to identify some obstacles faced by women who desire the motherhood by using other people’s genetic material. Method: The essay had a focus on available collected testimonies from two selected virtual space aimed at women involved with the AHR process. The participants’ comments were examined and classified considering the obstacles they had about their experience and doubts related to their motherhood projects. Results: The reports analysis permitted the identification of a series of objective and subjective problems faced by women who wanted the motherhood with the donation of genetic material, and appreciating blogs as a place to exchange and share information. The virtual space is important in many situations: encouragement to the process of decision, or not, related to the AHR to get the pregnancy; genetic relationship needs, or not, to build a family; sociocultural development related to blood and family bonds; sympathy before the related experiences; sharing the experiences and knowledge built; support to other women; oocyte donation as a solution to an expensive high technological treatment; facing the prejudice about the use of given gametes; exposing the diagnostic of infertility to do the single parent motherhood; discussion about age and some disorders as restriction factors to motherhood. Conclusion: Blogs have been an important discussion forum where it is possible to share doubts, to know and explain the ambiguity ideas about the theme. Anonymity seems to benefit the experiences exchanged. Information allied to experiences may provide observation about AHR, and help to deconstruct barriers and change values and attitudes about this theme.